Cognitive emotion regulation and psychopathology across cultures: A comparison between six European countries. (August 2016) - Potthoff, Sebastian; Garnefski, Nadia; Miklósi, Monika; Ubbiali, Alessandro; Domínguez-Sánchez, Francisco Javier; Martins, Eva Costa; Witthöft, Michael; Kraaij, Vivian
Abstract: Use of cognitive emotion regulation strategies in response to stressful life events varies by country, though research has been limited to comparisons between American and Asian cultures. This study aimed to compare six European countries to investigate cross-cultural differences in the use of cognitive strategies and test if the relationship between specific strategies and psychopathology varies across countries. Data arrays were collected from the Netherlands, Hungary, Spain, Italy, Portugal and Germany (N = 1553) and cross-cultural measures of cognitive emotion regulation using the Cognitive Emotion Regulation Questionnaire (CERQ) were included. Measures of depression and anxiety were also included. Results showed significant differences on all the subscales of the CERQ. Most notably, there were differences on strategies that have been linked to symptoms of psychopathology; overall northern European countries (Germany and Netherlands) made less use of strategies such as rumination, catastrophizing, and other-blame, when compared to southern and eastern European countries (Spain, Italy, Portugal, and Hungary). The direction of the relationships between specific strategies and symptoms of psychopathology was consistent across countries. Although there were cross-cultural differences in the use of cognitive strategies, the consistent relationship between strategies and psychopathology across countries supports the idea of a trans-cultural approach to treat psychopathology. Highlights: Cross-cultural differences in emotion regulation have been observed across Europe. The use of maladaptive emotion regulation was the most prominent in Southern Europe. The link between cognitive strategies and psychopathology was consistent across Europe.